Genetically engineered zebrafish liver (ZF-L) cells as an in vitro source for zebrafish acetylcholinesterase (zfAChE) for the use in AChE inhibition assays - Heinrich, Patrick; Braunbeck, Thomas (Toxicology in vitro, 2018)
Zebrafish acetylcholinesterase (zfAChE) preparations employed for the evaluation of acetylcholinesterase inhibition are usually extracted from animal tissues, a procedure suffering from both technical and ethical limitations, which may be alleviated using an in vitro expression system for enzyme generation. For this end, a protocol for stable transfection and selection of zebrafish liver (ZF-L) cells using an adapted expression plasmid “ZF-L Exp” was developed. After insertion of zfAChE cDNA, the enzyme was efficiently expressed in transgenic ZF-L cell lines, which were then used as a high yield source of zfAChE activity for acetylcholinesterase (AChE) inhibition assays. An adapted assay protocol was used to demonstrate the effects of carbaryl, dichlorvos and caffeine as model AChE inhibitors towards zfAChE. Dimethyl sulfoxide (DMSO) was also strongly inhibitory towards zfAChE. Finally, we provide data on the stability of zfAChE enzyme preparations. The novel test system provides a promising in vitro test system for the assessment of zfAChE inhibition.
Received 19 January 2018, Revised 4 May 2018, Accepted 1 June 2018, Available online 2 June 2018
Gesehen am 27.08.2019